Assessing Speaking Skills: The What’s and the How’s - Thanh Lam, Trung (Issues in Language Instruction, 2018)
Assessing speaking skills in TEFL has been a neglected or unmanageable area of instruction in the context of Vietnam’s senior high schools. Furthermore, administering end-of-semester speaking tests in largescale classrooms has been an impossible mission. This workshop will suggest tips and tools to make the assessment of these skills manageable.